Fibromyalgia Syndrome - Choy, Ernest (Oxford rheumatology library., 2009)
Fibromyalgia is a common condition affecting 2-4% of the population. It is characterised by chronic widespread pain, fatigue, depression and anxiety. Due to the absence of objective diagnostic tests and an overlap with other conditions there is often a signifcant delay in diagnosis. It is therefore vital that clinicians can recognise the condition and diagnose early to avoid anxiety and frustration for the patient. This concise practical pocketbook helps rheumatologists and general practitioners to diagnose patients and best manage patients with fibromyalgia.